2008
DOI: 10.1175/bams-89-3-347
|View full text |Cite
|
Sign up to set email alerts
|

Hurricanes and Global Warming: Results from Downscaling IPCC AR4 Simulations

Abstract: A new technique for deriving hurricane climatologies from global data, applied to climate models, indicates that global warming should reduce the global frequency of hurricanes, though their intensity may increase in some locations. A range of techniques has been brought to bear on this question. The most straightforward approach is to quantify the response of tropical cyclone activity to past climate change using historical climate and storm records, but this approach is limited by the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
804
4
10

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 775 publications
(853 citation statements)
references
References 42 publications
35
804
4
10
Order By: Relevance
“…Emanuel [1995] identified a nondimensional parameter that regulates the time needed for an incipient disturbance to saturate the middle troposphere to allow for intensification; larger values imply longer gestation. It is also a likely explanation for the decrease in storm frequency with warming observed in global climate models [e.g., Emanuel et al, 2008;Camargo et al, 2014]. The parameter is defined as:…”
Section: Mid-tropospheric Moisture Contentmentioning
confidence: 99%
“…Emanuel [1995] identified a nondimensional parameter that regulates the time needed for an incipient disturbance to saturate the middle troposphere to allow for intensification; larger values imply longer gestation. It is also a likely explanation for the decrease in storm frequency with warming observed in global climate models [e.g., Emanuel et al, 2008;Camargo et al, 2014]. The parameter is defined as:…”
Section: Mid-tropospheric Moisture Contentmentioning
confidence: 99%
“…Most glaring is its dimensional inconsistency. Moreover, recent studies by Nolan et al (2007, hereafter N07) and Nolan and Rappin (2008, hereafter N08) showed that the index predicted an increase in genesis in an environment of increasing SST, whereas numerous GCM simulations with and without regional downscaling show a general decrease in genesis with increasing SST due to global warming (Sugi et al, 2002;Yoshimura et al, 2006;Bengtsson et al, 2007;Emanuel et al, 2008;Knutson et al, 2008), albeit with much regional variability.…”
Section: A Pseudo-indexmentioning
confidence: 99%
“…However, in Bangladesh, overcrowding in the mainland drives the poor and landless people to live in the coast where they are exposed to frequent cyclone and storm surges (IPCC 1996;Rahman 2004). Staying alive, and livelihood security is central to the welfare of the coastal communities (Mutahara et al 2013); and increasingly perilous as the frequency of cyclonic storm-surges are increasing due to climate change (Emanuel et al 2008).…”
Section: Introductionmentioning
confidence: 99%